(untitled) (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2004)
A new approach to establishing generalized Taylor’s expansions is used to prove the trigonometric analogue of the Taylor’s formula. We derive point-wise estimates of the error in the trigonometric interpolation and approximation by convolutional linear operators.